Meta-Analysis of Risk Factors for Lower Extremity Amputation in Diabetes Mellitus Patients with Foot Ulcers - Septiani, Anissa Eka; Rahardjo, Setyo Sri; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Diabetic foot ulcer is a complication of diabetes mellitus which costs high, takes long wound care, increases mortality, morbidity and causes non-traumatic amputation. There are risk factors that are thought to be the cause of lower limb amputation in diabetic foot ulcers, namely peripheral artery disease, hypertension and gender. This study aims to estimate the influence of peripheral artery disease, hypertension and gender on the risk of lower limb amputation in diabetes mellitus patients with leg ulcers.Subjects and Method: Meta-analysis studies and systematic reviews were applied to this study using electronic databases of Pubmed, Scopus, Google Scholar, and Springer Link. The keywords to search for articles are as follows: